2009
DOI: 10.1074/jbc.m807715200
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Activator Function of the Novel RAD51- and RAD51B-binding Protein, Human EVL

Abstract: The RAD51 protein is a central player in homologous recombinational repair. The RAD51B protein is one of five RAD51 paralogs that function in the homologous recombinational repair pathway in higher eukaryotes. In the present study, we found that the human EVL (Ena/Vasp-like) protein, which is suggested to be involved in actin-remodeling processes, unexpectedly binds to the RAD51 and RAD51B proteins and stimulates the RAD51-mediated homologous pairing and strand exchange. The EVL knockdown cells impaired RAD51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 65 publications
(50 reference statements)
2
29
0
3
Order By: Relevance
“…Over-expression of this gene has been shown to cause cell cycle delay and apoptosis (27, 28). The RAD51L1 gene is not ubiquitously expressed, but it is significantly expressed in breast cancer-derived MCF7 cells (29). A recent GWAS identified a SNP in this gene, rs999737, to be associated with breast cancer risk (16).…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of this gene has been shown to cause cell cycle delay and apoptosis (27, 28). The RAD51L1 gene is not ubiquitously expressed, but it is significantly expressed in breast cancer-derived MCF7 cells (29). A recent GWAS identified a SNP in this gene, rs999737, to be associated with breast cancer risk (16).…”
Section: Discussionmentioning
confidence: 99%
“…PSF is also reported to interact directly with RAD51D in vitro and to play a role in maintaining sister chromatid cohesion [1193]. Additional proteins that interact with RAD51 and its paralogs are being identified [1194].…”
Section: Additional Factors That Promote Rad51 Focus Formation and Stmentioning
confidence: 96%
“…Molecular studies of the RAD51L1 protein suggest its main function is to promote homologous recombination repair; specifically, the protein contributes to genome integrity maintenance in response to UV-induced damages (Havre et al 1998; Takata et al 2000). In breast cell lines, it has been shown that both transcription and protein levels of RAD51L1 are down-regulated by over-expression of EZH2, a transcriptional repressor previously linked to aggressive and metastatic breast cancers; RAD51L1 may also partner with the protein EVL (Ena/Vasp-like) to stimulate inappropriate RAD51-mediated recombination in breast cancer cell lines (Takaku et al 2009; Zeidler et al 2005). …”
Section: Introductionmentioning
confidence: 99%